Biomimicking Antibacterial Opto‐Electro Sensing Sutures Made of Regenerated Silk Proteins. Issue 1 (10th November 2020) - Liu, Mengwei; Zhang, Yujia; Liu, Keyin; Zhang, Gai; Mao, Ying; Chen, Liang; Peng, Yinbo; Tao, Tiger H.
Abstract: Surgical sutures play an important role across a wide range of medical treatments and a wide variety exist, differing in strength, size, composition, and performance. Recently, increasing interest has been paid to bioactive and electronic sutures made of synthetic polymers, owing to their ability to reduce inflammation as well as medically and/or electronically facilitate wound healing. However, integrating sensing capabilities into bioactive sutures without adversely affecting their mechanical strength, biocompatibility, and/or bioactivity remains challenging. In this work, a set of biomimicking, antibacterial, and sensing sutures based on the regenerated silk fibroin is designed and fabricated. These sensing sutures, inspired by the "core–shell" multilayered structure of natural spider‐silk fibers, are hierarchically structured and heterogeneously functionalized to allow for the integration of multiple, clinically favorable functions into one suture device. These functions included: reducing inflammation and bacterial infection in wound sites, measuring tension of both the tissue and suture, and aiding tissue healing via multi‐modal controlled drug and growth factor release. Critically, these functions are coupled with real‐time optical and electronic monitoring capabilities. This approach provides greater insight into multifunctional sutures with inherent sensing capabilities and offers enormous potential in both therapeutic and diagnostic applications. Abstract : A set of biomimicking, antibacterial, and sensing sutures made of regenerated silk fibroin inspired by natural spider‐silk fibers is presented. These sensing sutures are hierarchically structured and heterogeneously functionalized so as to integrate multiple, clinically favorable functions into one suture device. These functions include reducing inflammation, antibacterial activity, tension measurements, aiding tissue healing, and opto‐electro monitoring.